A constraint-based, efficiency optimisation approach to network-level pavement maintenance management. Issue 11 (2nd November 2019) - Hankach, Pierre; Lorino, Tristan; Gastineau, Pascal
Abstract: Network-level pavement maintenance programming is characterised by its high computational complexity. In this article, a novel modelling to solve this problem efficiently is proposed. In this modelling, careful care has been taken to reduce the search space and formulate the original problem as one of the well-known problems of the literature on mathematical optimisation. Efficient algorithms can therefore be used to find a solution. According to this approach, the maintenance programming problem is divided into two sub-problems: (i) the first performs a reduction of the search space by filtering road section maintenance alternatives based on technical criteria; (ii) the second computes a road network-level maintenance program by optimising efficiency subject to budget constraints. The section-level filtering of alternatives is modelled as a constraint satisfaction problem and solved using appropriate constraint satisfaction algorithms. The network-level maintenance programming is modelled as a generalised assignment problem, whose resolution is well documented in the literature on optimisation. This approach has shown to be very effective, with strong computational performances for different road network sizes.